Natural Tetraploidy in Tribulus alatus Del. - Bhansali, A. K.; Bhandari, M. M. (Indian Forester, 1980)
The present cytological studies in T. alatus shows n=6, while the number previously reported was n=12. The latter appears to be an allopolyploid of recent origin.